Barriers to access and organization of primary health care services for rural riverside populations in the Amazon - Luiza Garnelo; Rosana Cristina Pereira Parente; Maria Laura Rezende Puchiarelli; Priscilla Cabral Correia; Matheus Vasconcelos Torres; Fernando José Herkrath (BMC, 2020)
Abstract Background The ways of life in the Amazon are diverse and not widely known. In addition, social inequities, large geographic distances and inadequate health care network noticeably limit access to health services in rural areas. Over the last decades, Brazilian health authorities have implemented fluvial mobile units (FMU) as an alternative to increase access and healthcare coverage. The aim of the study was to identify the strategies of access and utilization of primary health care (PHC) services by assessing the strengths and limitations of the healthcare model offered by the FMU to reduce barriers to services and ensure the right to healthcare. Methods Qualitative and ethnographic research involving participant observation and semi-structured interviews. Data collection consisted of interviews with users and health professionals and the observation of service organization and healthcare delivered by the FMU, in addition to the therapeutic itineraries that determine demand, access and interaction of users with healthcare services. Results Primary care is offered by the monthly locomotion of the FMU that serves approximately 20 rural riverside communities. The effectiveness of the actions of the FMU proved to be adequate for conditions such as antenatal care for low-risk pregnancy, which require periodic consultations. However, conditions that require continued attention are not adequately met through the organization of care established in the FMU. The underutilization of the workforce of community health workers and disarrangement between their tasks and those of the rest of the multi-professional team are some of the reasons pointed out, making the healthcare continuity unfeasible within the intervals between the trips of the FMU. From the users' perspective, although the presence of the FMU provides healthcare coverage, the financial burden generated by the pursuit for services persists, since the dispersed housing pattern requires the locomotion of users to reach the mobile unit services as well as for specialized care in the urban centers. Conclusions The implementation of the FMU represents an advance in terms of accessibility to PHC. However, the organization of their activity uncritically replicates the routines adopted in the daily routine of health services located in urban spaces, proving to be inadequate for providing healthcare strategies capable of mitigating social and health inequalities faced by the users.